The right to the city, the public interest and the human development. relations and complementarities (2008)
Actual urban life implies the deprivation of adequate and acceptable satisfaction of the basic’s needs and elemental rights of its inhabitants. The severe situation is evident when we take count of the social exclusion and the spatial segregation that harms the social coexistence around the world. To overcome this context is due to have clarity about Right to the City’s concept and implications and start the social changes needed for its effectiveness. The right to the city, as a postmodern challenge to guarantee the dignity of life in the urban contexts, demands the effectiveness of the human, social and collective rights, and also a paradigmatic change leaned on the civic citizenship, the inclusive urban government, the prevalence of the public interest, as a fundamental value of the urban social life and the process of human development conceived as a social and cultural construction. This right is referred to the access to the city perceived as integrity of goods, services and opportunities. The access implies that all its inhabitants could benefit and use, without discrimination all the city offers.